Medical Writing for Non-Native English Speakers: Help for Usage of Articles - Škrbić, Ranko; Igić, Rajko (Scripta Medica, 2019)
Many non-native speakers, especially those whose mother language has no articles (like Slavic languages) make mistakes when they speak or write English. This may sound rather rough to English-speaking listeners or readers. To improve their command of the language and the usage of articles, individuals for whom English is a second language should review the usage of articles from time to time. We prepared a short text on this subject and also included exercises from the medical publications. Key words: articles, definite article, indefinite articles, zero article, omitted article, non-native speakers, exercises.